CONTROL OF CODLING MOTH (CYDIA POMONELLA L.) BY APPLICATION OF INSECTICIDE CHLORANTRANILIPROLE - Vuković, Slavica; Žunić, Antonije; Šunjka, Dragana; Lazić, Sanja; Petrović, Miloš; Laćarac, Nikola (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
In the last few decades, intensive apple farming has required increasing technology and knowledge to ensure a high yield and product quality. In pest and disease management in apple orchards, in addition to various control tools including agrotechnical and biological ways of protection, it is necessary to apply different chemical pesticides for plant protection several times during the year. The codling moth is one of the most important orchard pests, particularly in apples. It often causes high damage, resulting in premature fruit drop, larvae-eaten fruit, and difficulties in preserving fruit during storage, primarily due to untimely and unsuitable protection. In 2023 and 2024, the trials were carried out according to the standard EPPO methods. This study aimed to assess the efficacy of plant protection product based upon chlorantraniliprole (200 g a.i./L, SC), against the codling moth in apple protection. In the apple orchard (variety Idared, Golden Delicious and Gala) at Budisava and Mala Remeta localities (Vojvodina, Serbia), the product were foliar applied by backpack sprayer at a concentration of 0.02%. The experiment was set up in four replications in randomized block design. By visual examination the presence of C. pomonella eggs was registered, and the hatching of caterpillars of the first (2023) and second (2024) generation of this pest was underway. The efficacy of the tested insecticide was evaluated based on the number of damaged fruits. The efficacy of the insecticide was calculated according to Abbott, and the significance of differences (ANOVA) and LSD test for the confidence interval of 95%. In 2023, fourteen days after application the efficacy chlorantraniliprole was 95.3% at the locality Budisava, while in locality M. Remeta efficacy was 92.4%. After 22 days, the product showed good efficacy which ranged from 88.2-93.0%, depending on the locality. In 2024, 14 days after application, the efficacy was 93.7% at the locality Budisava, while in locality M. Remeta efficacy was 89.8%. After 25 days, the insecticide showed good efficacy which ranged from 89.5-90.6%, depending on the locality. In both years, the number of damaged apples in the variants where applied chlorantraniliprole was significantly lower compared to the control. In the studied localities, in bouth years, C. pomonella displayed notable susceptibility to  chlorantraniliprole belonging to the diamides groups. This indicates that this insecticide can still be effectively used for managing this economically significant pest in apple orchards, as long as the anti-resistance strategy is strictly adhered to.